The limits to exercise performance and the future of fatigue research - Marino, FE; Gard, M; Drinkwater, EJ (South African Journal of Sports Medicine, 2012)
The study of human fatigue stretches back centuries and remains a significant part of medical and social discourse. In the exercise sciences fatigue is routinely related to the ability to produce muscle force or to the recovery from force decrements. However, the study of fatigue has by virtue of the experimental paradigm excluded the subjective sense a person attributes to an event or experience, thus reducing our overall understanding of the fatigue process. Modern studies report the causes of fatigue as either central or peripheral in origin. Although useful, this dichotomy can also exclude the individual subjective assessment. Furthermore, adhering dogmatically to set parameters is likely limiting the advancement of our understanding. A more realistic paradigm would permit the individual to use the sensory cues to adjust the effort along with the fatigue process rather than rely purely on feedback mechanisms. Therefore, bringing feedforward mechanisms of the brain into fatigue research perhaps represents the next phase in the unravelling of the fatigue process.